Meningkatkan Prestasi Belajar Pendidikan Agama Kristen Melalui Penggunaan Media Pembelajaran “Quizizz” di Masa Pandemi Covid-19 - Priskila Issak Benyamin; Yuel Sumarno; Ucok Sinaga (Fakultas Ilmu Keguruan dan Pendidikan, Universitas Kristen Indonesia, 2021)
Online learning in the pandemic era tends to make students passive in class. Therefore, researchers use Quizizz Learning media to increase student activity and achievement in PAK learning at SMA Negeri 16 Jakarta in the covid-19 era. The purpose of this study was to determine the increased inactiveness and learning achievement of Christian Religious Education for class XII students of SMA Negeri 16 West Jakarta through the learning media